Bauran Pemasaran Pada Usaha Cake Dan Bakery “Hari-Hari” Di Kota Manado - Tobing, Ica Maria; Pangemanan, Paulus Adrian; Lolowang, Tommy Fredy (AGRI-SOSIOEKONOMI, 2024)
This research aims to describe the marketing mix at the Cake and Bakery "Hari-hari" business in Manado City. This research was conducted for 1 month, from June to July 2023. The sampling method used in the study was accidental sampling. Primary data was collected through interviews guided by a list of questions that had been prepared previously and the results of direct observations at the research site. Secondary data is obtained from the library, namely written sources and books obtained from local books and the internet through google scholar in the form of books, articles, journals and theses related to the research topic, namely the marketing mix in business. The data analysis method used in the research is descriptive. The results of the study explain that the marketing mix in the Cake and Bakery "Hari-hari" business has not fully implemented the marketing mix perfectly where the seven elements of the product marketing mix, price, promotion, place, people, process, physical appearance have been implemented properly but there is one element that has not been maximized, namely promotion. The current promotion is not maximized.